2022
DOI: 10.1002/csr.2243
|View full text |Cite
|
Sign up to set email alerts
|

Identifying different sustainable practices to help companies to contribute to the sustainable development: Holistic sustainability, sustainable business and operations models

Abstract: Companies are facing pressure in order to reduce their environmental impact.However, the managerial tools and frameworks to bring sustainability into practice are in their infancy. This paper is encompassed on the development of the Theory of Corporate Sustainability, and this work offers the practical implication of the theory to provide researchers and managers with a tool to analyse how companies integrate sustainability among their strategies and operations. The methodology has been based on the use of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 86 publications
(115 reference statements)
0
10
0
Order By: Relevance
“…However, the achievement of the Sustainable Development Goals (SDGs) comes with significant challenges (Grover et al, 2018). The studies carried out show that progress is being made towards achieving the SDGs (Chindasombatcharoen et al, 2021; Haughton & Keane, 2021; Lyytimäki et al, 2020; Sanchez‐Planelles et al, 2022), but neither the speed nor the scale are adequate to improve the current levels of poverty, hunger, education, and health that characterize certain territories as well as to reduce climate emergency or discrimination (United Nations, 2019, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, the achievement of the Sustainable Development Goals (SDGs) comes with significant challenges (Grover et al, 2018). The studies carried out show that progress is being made towards achieving the SDGs (Chindasombatcharoen et al, 2021; Haughton & Keane, 2021; Lyytimäki et al, 2020; Sanchez‐Planelles et al, 2022), but neither the speed nor the scale are adequate to improve the current levels of poverty, hunger, education, and health that characterize certain territories as well as to reduce climate emergency or discrimination (United Nations, 2019, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of literature tend to use case studies of firms that have incorporated CE practices either as a transition or by focusing on start‐ups that have been set up based on CBM fundamentals (Bocken et al, 2016; Daddi et al, 2019; Khan et al, 2020; Ranta et al, 2018; Rovanto & Finne, 2023; Sanchez‐Planelles et al, 2022; Sharma et al, 2021; Sohal et al, 2022). The use of case studies tends to show a positive view on CE transition as most cases studied are typically firms that have taken the initial steps for a transition.…”
Section: Circular Business Practicesmentioning
confidence: 99%
“…Considering the outcome of sustainability practices, organizations all over the world are trying to involve different forms of sustainability activities in their operations (Bai, 2022; Danso et al, 2019; Marin et al, 2017; Panwar et al, 2016). Earlier research revealed the influence of different factors such as the nature of businesses, operations, products, services, and customers' engagement on organizational sustainability practices that varies within and across businesses, sectors, countries, and contexts (Duanmu et al, 2018; Sanchez‐Planelles et al, 2022; Upadhaya et al, 2018). In addition to those contingency factors, organizational strategies, more specifically business strategies, are also found to have significant influences on organizations' engagement in sustainable practices (Chen et al, 2018; Kong et al, 2020; Lin et al, 2021; Romme et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the lack of knowledge in those areas, this study investigates the relationship between organizational slack resources and variations in business strategies and their subsequent influence on different aspects of sustainability practices. Empirical evidence of the influence and impact of slack resources on business strategies as well as on sustainability practices could help managers to identify appropriate matching sustainability practices to improve financial performance and gain long‐term competitive advantages (Chen et al, 2018; Kong et al, 2020; Lin et al, 2021; Sanchez‐Planelles et al, 2022; Upadhaya et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation